Potamogetonaceae Dumort. - rdestovité - Kaplan, Z. (Zdeněk) (2010)
A comprehensive treatment of the family Potamogetonaceae and the genus Potamogeton, Groenlandia and Stuckenia in the Czech Republic is provided. It includes description of the genera, detailed morphological description of species, nomenclature, notes on variation, ecology, distribution and supplementary comments.